Characterization of Linseed Varieties Based on Seed Coat Colour - D. KHARE,; S.S. SHUKLA,; P. NAIR,; M.S. BHALE, (Seed Research, 2026)
Seed coat colour is an important trait for verification and protection of linseed varieties. Due to continuous note it is very difficult to place the varieties in the neighboring notes. By naked eye the varieties were categorized in five states with considerable amount of error. RHS colour chart reduced the error and grouped the varieties in five states, whereas Hunter's colour lab categorized the linseed varieties in eight states with minimum error.